Two new species of Pleroma (Melastomataceae) from Espírito Santo, Brazil - Fraga, Claudio Nicoletti De; Guimarães, Paulo José Fernandes (Phytotaxa, 2014)
Pleroma marinana and P. penduliflora, two new species of Pleroma (Melastomataceae) from the dry seasonal Atlantic forest of Espírito Santo, Brazil, are described and illustrated, with their affinities and diagnostic characters discussed. Pleroma marinana is similar to Tibouchina radula and T. oreophila while Pleroma penduliflora is similar to Pleroma heteromalla, Tibouchina bahiensis and T. formosa. According to the criteria of the IUCN Red List, T. marinana must be included in the vulnerable and T. penduliflora in the endangered category.